Impact of ankyloglossia on the language development of children - DURMUŞ KOCAASLAN, FATMA NİHAL; BARIŞ, HATİCE EZGİ; BORAN, PERRAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Ankyloglossia is a benign anomaly of the tongue which may cause functional limitation. Evidence regarding the impact of ankyloglossia on children's language development is limited. We aimed to evaluate the language development of children born with ankyloglossia. Patients and Methods: Children diagnosed with ankyloglossia were followed up prospectively. Demographic characteristics, degree of ankyloglossia assessed by Hazelbaker score in infancy and its effects on breastfeeding were evaluated. Language development was tested by the Turkish version of the Test of Early Language Development-Third Edition and the Denver II Test at 3-5 years of age. Results: Out of 53 children diagnosed with ankyloglossia, 38 (71.7%) children had language development testing and were included into the study. Significant ankyloglossia was detected in infancy in 10 of these children (26.3%). Median time of exclusively breastfeeding was not different according to the severity of ankyloglossia. All children evaluated with Denver II Test were developmentally normal in all domains. Scores of Test of Early Language Development-Third Edition were not different between children with and without significant ankyloglossia. Conclusion: Long term language development of children with ankyloglossia was not adversely affected. Parents should be appropriately informed and efforts must be paid to prevent unnecessary surgical interventions concerning language delay.
Keywords: Ankyloglossia; Children; Language development; TONGUE-TIE DIVISION; SPEECH; DIAGNOSIS; INFANTS; PERCEPTION; SURGERY